The forgotten cottage - Ellis, Courtney, 1992- (Berkley, 2022)
"Connected through time to her great-grandmother by a shared English countryside home, an American nurse tries to piece together her family's tangled history. England, 2019: Audrey Collins knows only two things about her beloved grandmother's past: She was born into nobility and she immigrated to America at seventeen years old. So when Audrey inherits her gran's home in North Yorkshire, she arrives expecting a sprawling country estate fit for lords and ladies. Instead, she finds an abandoned stone cottageperfectly preserved as Gran left it when she fled in 1941-ration book and all-and begins to uncover what secrets her family has been keeping. France, 1915: Lady Emilie Dawes is working as a nurse on the Western Front, grateful to have escaped the restraints of her restrictive, privileged home life. But the independence she fought hard to earn is suddenly jeopardized when a familiar man shows up in one of her hospital beds. Facing him means facing her past and the decisions she made in fear. As the war rages around her, Emilie realizes she cannot continue running from who she is until she decides who she truly wants to be. Over a hundred years apart, Audrey and Emilie each struggle to find purpose, love, and a place to call home in this enchanting familysaga celebrating the courage of underestimated women-and the power a secret can hold across generations"--